2022
DOI: 10.1101/2022.03.13.483276
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Genetic History of Continuity and Mobility in the Iron Age Central Mediterranean

Abstract: The Iron Age saw the expansion of Phoenician and Greek colonies across the Mediterranean and the rise of Carthage as the major maritime power of the region. These events were facilitated by the ease of long-distance travel following major advances in seafaring. We know from the archaeological record that trade goods and materials were moving across great distances in unprecedented quantities, but it is unclear how these patterns correlate with human mobility. To investigate population mobility and interactions… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 62 publications
0
15
0
Order By: Relevance
“…We collected whole genomes from 204 individuals across 53 archaeological sites in 18 countries spanning Europe and the Mediterranean (Figure 1 - figure supplement 1), 26 of these individuals were recently reported (Moots et al, 2022). This collection includes the first historical genomes from present-day Armenia, Algeria, Austria, and France.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We collected whole genomes from 204 individuals across 53 archaeological sites in 18 countries spanning Europe and the Mediterranean (Figure 1 - figure supplement 1), 26 of these individuals were recently reported (Moots et al, 2022). This collection includes the first historical genomes from present-day Armenia, Algeria, Austria, and France.…”
Section: Resultsmentioning
confidence: 99%
“…The 204 ancient genomes reported in this study, 26 of which were recently reported in (Moots et al, 2022), represent a subset of samples screened from 53 archaeological sites across 18 countries.…”
Section: Dna Extraction Library Preparation and Sequencingmentioning
confidence: 99%
See 3 more Smart Citations